Effect of Azadirachta indica and Senna siamea Decoction on CD4+ and CD8+ Level, Toxicological, and Antioxidant Profile in HIV/AIDS Positive Persons - Oumarou Goni Hamadama; Mbah Ntepe Leonel Javeres; Nyunaï Nyemb; Medou Mba Fabrice; Pettang Tomen Manuela Elsa (Journal of Toxicology)
Acquired immune deficiency syndrome (AIDS) is a major public health problem affecting several countries with predominance in black Africa. Faced with therapeutic failure caused by resistance and supply disruptions, searching for other antiretroviral agents, in particular from natural sources, becomes necessary. Given popular consumption of Azadirachta indica and Senna siamea decoction in the Northern Cameroon region and the traditionally attributed antiretroviral value, information on its efficacy and safety consumption is relevant to confirm its use. A total of 297 participants aged 18–52 and HIV-positive were recruited and divided into 3 groups: one taking only the decoction (group 1), another taking only antiretroviral therapy (ARTs) (group 2), and finally, one taking the decoction and antiretroviral (group 3). During 6 months, all the participants of the concerned groups consumed daily (morning and evening) 250 mL of Azadirachta indica and Senna siamea decoction. CD4+ and CD8+ levels were measured by flow cytometry. Hepatic and renal toxicity and oxidative stress were evaluated spectrophotometrically by measuring ALT, AST, ALP, BUN, CREAT, SOD, CAT, and GSH parameters. We note an increase in the CD4+ level of the three groups with values much more pronounced in the group treated by ARTs + decoction, from 328 ± 106 to 752 ± 140. Group 2 presented not only biological signs of hepatic and renal toxicity but also significant oxidative stress. No signs of toxicity were detected in the other groups. The study concludes that a decoction of Azadirachta indica and Senna siamea stimulates the production of CD4+ and is not toxic. On the contrary, it would reduce the toxicity caused by ARTs intake.